O2 supplementation to secure the near-infrared spectroscopy determined brain and muscle oxygenation in vascular surgical patients: a presentation of 100 cases - Rokamp, Kim Z.; Secher, Niels H.; Eiberg, Jonas P.; Lonn, Lars; Nielsen, Henning B. (Frontiers in Physiology, 2014)
This study addresses three questions for securing tissue oxygenation in brain (rScO2) and muscle (SmO2) for 100 patients (age 71 ± 6 years; mean ± SD) undergoing vascular surgery: (i) Does preoxygenation (inhaling 100% oxygen before anesthesia) increase tissue oxygenation, (ii) Does inhalation of 70% oxygen during surgery prevent a critical reduction in rScO2 (<50%), and (iii) is a decrease in rScO2 and/or SmO2 related to reduced blood pressure and/or cardiac output?Intravenous anesthesia was provided to all patients and the intraoperative inspired oxygen fraction was set to 0.70 while tissue oxygenation was determined by INVOS 5100C. Preoxygenation increased rScO2 (from 65 ± 8 to 72 ± 9%; P < 0.05) and SmO2 (from 75 ± 9 to 78 ± 9%; P < 0.05) and during surgery rScO2 and SmO2 were maintained at the baseline level in most patients. Following anesthesia and tracheal intubation an eventual change in rScO2 correlated to cardiac output and cardiac stroke volume (coefficient of contingence = 0.36; P = 0.0003) rather to a change in mean arterial pressure and for five patients rScO2 was reduced to below 50%. We conclude that (i) increased oxygen delivery enhances tissue oxygenation, (ii) oxygen supports tissue oxygenation but does not prevent a critical reduction in cerebral oxygenation sufficiently, and (iii) an eventual decrease in tissue oxygenation seems related to a reduction in cardiac output rather than to hypotension.